The Role of Government Expenditure and Household Expenditure in Increasing Economic Growth in North Sumatra Province - Berutu, Saiful Ragatna; Lubis, Irsad (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
The economic growth of North Sumatra Province in 2023 was 5.01%. This growth is still below the average Indonesian economic growth of 5.05%. This study aims to analyze the role of government spending and household spending in increasing economic growth in North Sumatra Province. Researchers used panel data regression with government expenditure and household expenditure as the main independent variables and supplemented with the human development index and the average Bank Indonesia interest rate to obtain a more accurate regression equation in explaining economic growth in North Sumatra Province. Government expenditure consists of two variables, namely local government capital expenditure and central government capital expenditure. Meanwhile, household expenditure consists of two variables, namely household expenditure on food and household expenditure on non-food. The data covers 33 districts/cities over the period 2017-2022. The results of the analysis show that local government capital expenditure, central government capital expenditure, and household expenditure on food consumption have a positive and significant effect on economic growth. While household expenditure on non-food has a negative and significant effect on economic growth. For this reason, the government should allocate additional capital expenditure budgets each year and create programs to maintain people's purchasing power.